España y el golpe de estado contra De Gaulle - Karima Aït Yahia (Cahiers de Civilisation Espagnole Contemporaine)
The policy of good understanding with France, which Franco had initiated in 1957, was under threat by an episode of the Algerian War of Independence. Former French general Raoul Salan, who had taken refuge in Spain for his opposition to the policy of self-determination in Algeria, managed to escape the surveillance of the Francoist security forces to lead, in April 1961, the «putsch of the Generals». Salan received the active support of a group of Falangistas, and as demonstrated by our analysis of the major newspapers of the time, also had the sympathy of a part of public opinion. Franco's government, just like part of the press, took a hesitant attitude and did not express itself clearly. Our analysis also makes clear that in terms of foreign policy there was great diversity of opinion within the regime, since the more liberal newspapers wholeheartedly supported de Gaulle, as the legitimate president of the French Republic.